Monoclonal Antibody Therapy: The Development of a Liquid Chromatography Tandem Mass Spectrometry Method to Measure Rituximab Concentrations in Human Plasma - Kuhar, Ana (Department of Medicine, 2025)
The escalating global incidence of cancer has emphasised the urgency for innovative therapeutic strategies. Monoclonal antibodies (mAbs) have emerged as promising candidates for cancer treatment, driving the pursuit of tumour-targeted therapies. Rituximab (RTX) is one such mAb which has been of substantial interest in recent years as a therapy. The aim of this research project is to develop and optimise the extraction and quantification of RTX in human plasma using appropriate sample preparation techniques and liquid chromatography tandem mass spectrometry (LC-MS/MS) as the detection method. This was achieved by employing a bottom-up approach, culminating in the identification of a target peptide that serves as a representative of RTX. Sample preparation started with affinity binding purification using protein A bound to agarose beads. Based on the highly specific binding of protein A to the Fc region of immunoglobulins (IgG), this purification allowed for the specific extraction of IgG from plasma, including RTX, while all non-specific plasma proteins are excluded. The affinity binding process was optimised by investigating the addition of different volumes of protein A to purify the RTX from the matrix so that the available binding sites were not completely occupied by plasma IgG. The optimal volume of the protein A slurry used during the affinity binding purification procedure was found to be 200 µL. The extracted RTX molecules were subsequently digested while still bound to the protein A agarose beads, by incubation with trypsin, a protease that cleaves proteins by breaking the peptide bonds at the C-terminal side of the basic amino acids arginine and lysine. The optimal conditions for tryptic digestion were found to be in 25 mM Tris-HCl buffer at pH 8, including 10% acetonitrile and an enzyme-tosubstrate ratio of 1:20 (trypsin: RTX). Overnight incubation at room temperature was followed by a second addition of trypsin and a further 3 hours of incubation. Trypsin digestion of the bound proteins produced a large number of peptides, including the specific signature peptide (s-Pep) chosen to represent RTX. The sequence of this peptide is GLEWIGAIYPGNGDTSYNQK. The final process applied to extract the s-Pep from the total tryptic digest, was solid phase extraction (SPE), utilising Strata-X 33 µm polymeric reverse phase 30 mg / 1 mL SPE extraction cartridges, with elution using 70% acetonitrile containing 10% formic acid. Most of the method development was performed using a Sciex API-3200 triple quadrupole mass spectrometer for detection, coupled to an Agilent 1200 high performance liquid chromatography (HPLC) system used for chromatographic separation. The sensitivity of the Sciex API-3200 was however not adequate to analyse the s-Pep at the expected concentration range, and therefore, the project was concluded by transferring the analytical method to a Shimadzu Nexera X3 8050 LC-MS/MS system. Employing chromatographic separation on an Agilent Poroshell C18 column (2.1 x 50 mm 2.7-Micron) by applying a gradient mobile phase, resulted in the successful quantification of RTX at the required lower level of quantification of 12.5 µg/mL, and linearity throughout the analytical range of 12.5 – 300 µg/mL RTX in plasma